Kultura organizacyjna zespołów nauczycielskich – diagnoza i tendencje zmian. Komunikat z badań - Karwasz, Małgorzata Joanna (Teachers’ teams organizational culture – diagnosis and changes tendencies. Research message, 2024)
Organizational culture as a significant research problem applies to various levels and scopes of functioning of the entire education system. In the article, the teachers’ team is presented as one of the subcultures in the school organizational culture, on which the quality and course of the educational process depend to a large extent. The aim of the article is showing, based on own empirical research, the specifics of the teachers’ teams organizational culture in the Kuyavian-Pomeranian Voivodeship as well as verifying whether at the turn of the last several years the specificity of this culture has changed. When implementing research in the quantitative model, data was obtained to determine each level of organizational culture, i.e. assumptions, norms and values as well as artifacts. The conducted research has allowed to formulate several regularities regarding the specifics of organizational culture, including the trend of change, as well as conclusions and recommendations for educational practice. It was established, among others, that teachers, regardless of the period of the study, expect a change in organizational culture, currently – consisting in a stronger concentration in the position of school in the environment, earlier – in the internal matters of the team. A very clear change was also observed in the scope of perception of issues related to teamwork by respondents. It has been proven that a permanent feature of the organizational culture of the surveyed teams is its eclecticism, as well as the high attachment of respondents to building relationships with students. The research has shown that teachers see the need to undertake innovative initiatives, as well as limitate bureaucracy and strict control.